Spin-injection hall effect - Wunderlich, J.; Olejník, K.; Zărbo, L. P.; Amin, V. P.; Sinova, J.; Jungwirth, T. (Oxford University Press, 2017)
This chapter discusses the Spin-injection Hall effect (SiHE), another member of the spin-dependent Hall effects that is closely related to the anomalous Hall effect (AHE), the spin Hall effect (SHE), and the inverse spin Hall effect (iSHE). The microscopic origins responsible for the appearance of spin-dependent Hall effects are due to the spin-orbit (SO) coupling-related asymmetrical deflections of spin carriers. Depending on the relative strength of the SO coupling compared to the energy-level broadening of the quasi-particle states due to disorder scattering, scattering-related extrinsic mechanisms or intrinsic band structure-related deflection dominate the spin-dependent Hall response. Both the iSHE and the SiHE require spin injection into a nonmagnetic system. Similar to the AHE, a spin-polarized charge current flows in the case of the SiHE and the SO coupling generates the spin-dependent Hall signal.
CRIS-Team Scopus Importer:2023-03-27
Keywords: AHE; Anomalous Hall effect; Inverse spin Hall; ISHE; SHE; SiHE; Spin Hall effect; Spin-injection Hall